Diagnosis and Management of Pediatric Influenza in the Era of Rapid Diagnostics. (22nd November 2018) - Kitt, Eimear; Drew, Richard J; Cunney, Robert; Beekmann, Susan E; Polgreen, Philip; Butler, Karina; Zaoutis, Theoklis; Coffin, Susan E
Abstract: Influenza is a significant cause of childhood morbidity and death; it contributes to up to 16% of hospitalizations for respiratory illnesses worldwide. Novel rapid viral diagnostic tests, including molecular diagnostic tests, have the potential to significantly affect both time to diagnosis and selection of optimal anti-infective therapy. However, little is known about current treatment algorithms used in US hospitals. In this study, for hospitalized children in the United States, we aimed to define the current approaches to influenza diagnosis and treatment and to explore reasons for their potential variation. In this study, we aimed to define the current approaches to pediatric influenza diagnosis and treatment in US hospitals, and to explore reasons for their potential variation. Our results suggest a rise in the availability and use of rapid molecular diagnostic testing in addition to continued variability in anti-infective management, particularly with regard to antiviral use.